2021
DOI: 10.2147/prbm.s302551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Online Social Support and Perceived Social Support on the Relationship Between Perceived Stress and Problematic Smartphone Usage Among Chinese Undergraduates

Abstract: Purpose Recent research has identified a relationship between perceived stress and problematic smartphone usage. However, little is known about the underlying mediating and moderating mechanisms. The present study aimed to test the relationship between perceived stress and problematic smartphone usage as well as the mediating role of online social support and the moderating role of perceived social support among Chinese undergraduates. Patients and Methods A sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 56 publications
(71 reference statements)
1
34
1
Order By: Relevance
“…As a typical social use of smartphones, Facebook use has been found to enhance online social support (Liu and Yu, 2013). Online social support may have the same function as realistic social support (the care and support people feel or receive from real life), and can play a beneficial role (Cheung et al, 2017) or increase the risk of Internet addiction and smartphone addiction (Ding et al, 2013;Zhao et al, 2021). Others indicated that social smartphone use might not predict smartphone addiction.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical social use of smartphones, Facebook use has been found to enhance online social support (Liu and Yu, 2013). Online social support may have the same function as realistic social support (the care and support people feel or receive from real life), and can play a beneficial role (Cheung et al, 2017) or increase the risk of Internet addiction and smartphone addiction (Ding et al, 2013;Zhao et al, 2021). Others indicated that social smartphone use might not predict smartphone addiction.…”
Section: Introductionmentioning
confidence: 99%
“…College students are generally highly motivated to use smartphones and update them quickly, and they are also the fastest adopters and users of new applications and new programs ( 6 ). Recent researches show that college students generally own smartphones ( 7 , 8 ), excessive use of a smartphone can lead to problematic smartphone use ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Problematic smartphone use (PSU) refers to the excessive use of the smartphone or smartphone addiction in daily life, accompanied by dysfunction and symptoms similar to substance use disorder ( 11 ). PSU severity is associated with a wide variety of indicators, such as stress ( 10 , 12 , 13 ), symptoms of depression ( 12 , 14 , 15 ), poor sleep quality ( 15 , 16 ), and suicidal ideation ( 17 ). However, most of this research is based on cross-sectional studies, with only a few longitudinal studies examining risk or protective factors predicting PSU symptoms over time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations